Ø§Ù„Ù…Ù†Ø¸ÙˆÙ…Ø© Ø§Ù„Ø¨ÙŠÙ‚ÙˆÙ†ÙŠØ© ÙˆØ¹Ù†Ø§ÙŠØ© Ø£Ù‡Ù„ Ø§Ù„Ø¹Ù„Ù… Ø¨Ù‡Ø§ - Muhammad Yusram (Ø§Ù„Ø¨ØµÙŠØ±Ø©: Ù…Ø¬Ù„Ø© Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©, 2021)
Hadith is the second source of Islamic law after the Qur'an, obedience to the Messenger of Allah is also obedience to Allah SWT. The Prophet's Sunnah came to strengthen, explain and add new laws to the Qur'an. The scholars have paid great attention to preserving the sunnah, this is evidenced by their work in the science of hadith muá¹£á¹alaá¸¥, where they put down and establish rules for the acceptance and rejection of hadiths regarding mind and sanad. One of the most famous works in the science of muá¹£á¹alaá¸¥ hadith is al-Manáº“Å«mah al-BaiqÅ«nÄ«ah. This study aims to get to know al-Manáº“Å«mah al-BaiqÅ«nÄ«ah and its position among scholars in general and those who are involved in the science of hadith in particular as well as the intensity of the ulama's attention to this manmahÅ«mah. This research uses inductive and deductive descriptive methods, by extrapolating information related to the description and biography of al-BaiqÅ«nÄ« and what is related to the description of his book (al-Manáº“Å«mah al-BaiqÅ«nÄ«ah). In his research, the researcher achieved many results, including al-BaiqÅ«nÄ« does not have sufficient biography to show his identity, this manáº“Å«mah is one of the most succinct scientific observations in the science of muá¹£á¹alaá¸¥ hadith. Even though it is concise, this manzumah is highly accepted by those who are busy and deepen the science of hadith even though it contains criticism from some scholars. This is evidence of the great concern of the scholars for this manáº“Å«mah.